Exploring the Effect of Discrimination on Ethnic Minority Medical Students’ Mental Well-Being in the Netherlands - Omolayo Anjorin; Virginie L. Bakeroot; Albertine Zanting; Anja Krumeich; Jamiu O. Busari (Trends in Higher Education, 2023)
Racial discrimination is a global concern affecting education, including medical programs in the Netherlands. Covert racial discrimination in academia has been linked to adverse academic outcomes and unequal opportunities. This qualitative study explores the relationship between racism, well-being, and academic success among ethnic minority students in Dutch medical education. Conducted in 2021 at a southern Netherlands university, this research employed interviews to delve into the racial discrimination experiences of 11 diverse medical students. Utilising a phenomenological approach, the study conducted semi-structured interviews and applied thematic content analysis to understand how racial discrimination impacted the students’ well-being. The findings revealed the prevalence of both overt and covert racial discrimination in predominantly white educational environments. Ethnic minority students encountered discrimination that negatively affected their well-being and academic performance. Racism manifested in overt and covert ways, with students often normalising exclusionary and racist situations. Ethnic minority students reported experiencing more racial discrimination than their white European peers, resulting in feelings of exclusion and academic challenges. The study suggests that implementing student-centred inclusivity measures through structural and institutional changes, such as support structures, mentoring programs, and inclusive course content, can mitigate racial discrimination, enhance diversity and inclusion, and improve ethnic minority medical students’ mental well-being and academic performance. Addressing covert racism is crucial for fostering an equitable and inclusive educational environment. These findings underscore the importance of proactive action to combat racial discrimination in educational settings.